2021
DOI: 10.3390/app11125388
|View full text |Cite
|
Sign up to set email alerts
|

Gas Sensors Based on Localized Surface Plasmon Resonances: Synthesis of Oxide Films with Embedded Metal Nanoparticles, Theory and Simulation, and Sensitivity Enhancement Strategies

Abstract: This work presents a comprehensive review on gas sensors based on localized surface plasmon resonance (LSPR) phenomenon, including the theory of LSPR, the synthesis of nanoparticle-embedded oxide thin films, and strategies to enhance the sensitivity of these optical sensors, supported by simulations of the electromagnetic properties. The LSPR phenomenon is known to be responsible for the unique colour effects observed in the ancient Roman Lycurgus Cup and at the windows of the medieval cathedrals. In both case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 219 publications
(326 reference statements)
0
34
0
Order By: Relevance
“…Changes either in the bulk refractive index of the surrounding liquid or gas or in molecular events such as bioreceptor–analyte binding on the surface of the nanoparticles cause a detectable redshift in their light extinction spectrum [ 3 ]. Several excellent review papers can be found that demonstrate how to utilize this effect in a large variety of sensing applications [ 4 ], from gas sensing [ 5 ] to chemical and biosensing [ 6 , 7 ], e.g., for biomarker [ 8 , 9 , 10 ] or nucleic acid detection [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes either in the bulk refractive index of the surrounding liquid or gas or in molecular events such as bioreceptor–analyte binding on the surface of the nanoparticles cause a detectable redshift in their light extinction spectrum [ 3 ]. Several excellent review papers can be found that demonstrate how to utilize this effect in a large variety of sensing applications [ 4 ], from gas sensing [ 5 ] to chemical and biosensing [ 6 , 7 ], e.g., for biomarker [ 8 , 9 , 10 ] or nucleic acid detection [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In LabVIEW, the quasi-parallelism is easily performed by two separate loops [51,55]. This is why the complex representation of a pseudo code is not used at this point.…”
Section: Implementation Of the Control Of The Fbg In Labviewmentioning
confidence: 99%
“…Moreover, regarding amplification of signals obtained by plasmonic materials, graphene-based nanostructure composites can significantly increase the sensitive detection of analytes up to fM [90]. Owing to their sensitivity and the selectivity of the spectral location of the refractive index, SPR-based optical sensors have been widely investigated in sensing applications such as mercury ion detection [8,91], CO 2 detection [1], and gas sensors [2]. Some special emphasis on plasmonic nanostructures has been developed for the fabrication of novel surfaces, exposing high SPR-based optical sensors for phenolic compounds, such as GNP impregnation in TiO 2 structure-assisted hydroquinone detection [24], Au-and tyrosinase-modified graphene oxide film-introduced detection of phenol [9], and polymeric film-based phenol determination [92].…”
Section: Localized Surface Plasmon Resonance Phenomenon-based Optical Sensor For Phenolic Compoundsmentioning
confidence: 99%
“…Plasmonic resonance-based optical sensor technology has been considered to be an efficient method applied for sensing techniques of either indoor or outdoor carbon dioxide molecules [1], various gases [2], inorganic arsenic compounds [3], and pesticides [4]. Optical sensors have been known as simple analytical techniques to demonstrate numerous advantages such as facile design and effective detection, leading to promising potential applications in environmental metal ion monitoring [5].…”
Section: Introductionmentioning
confidence: 99%